When 'home languages' become 'holiday languages': teachers' discourses about responsibility for maintaining languages beyond English. Issue 3 (2nd July 2020) - Cunningham, Clare
ABSTRACT: Despite research evidence showing that home language maintenance is important both individually and societally, the task of managing and encouraging it has traditionally fallen to minority language communities and families, tending to lead to inter-generational language shift. Teachers' discourses about responsibilities for language maintenance, attrition and shift have not been researched adequately. This paper addresses this gap by offering a critical discourse analysis of research interviews with British primary school educators. Research on this topic is important because it is well known that teachers' attitudes impact on local policies and classroom practices. Findings show that teachers construct parents and children as responsible for maintenance and attrition of languages beyond English. Teachers hold varying attitudes on language maintenance, some perceiving it as important, whilst others do not. However, few participants claim any significant sense of personal or institutional responsibility for home language maintenance. Parents are construed as denying their children the chance to develop their home languages and children are negatively appraised for not taking opportunities to use them. Globally, teachers need to be empowered to challenge societal ideologies embedded in language policies and the education system should take a role in home language development to help prevent language shift.